Effect of Vitamin D supplementation on symmetric dimethyl arginine, asymmetric dimethyl arginine, homocysteine levels in rats being exposed to gamma radiation - Kahraman, Erdem; Ayan, Durmuş; Arıcıoğlu, Aysel; Akmansu, Müge (Asian Journal of Medical Sciences, 2021)
Background: Radiation causes to damage on endothelial cells by increasing oxidative stress. Vitamin D is also a potent anti-oxidant that facilitates balanced mitochondrial activities, preventing oxidative stress-related protein oxidation, lipid peroxidation, and DNA damage. Aims and Objective: We aimed to investigate the potential effect of vitamin D supplementation on levels of Hcy (homocysteine), ADMA (Asymmetric Dimethyl Arginine), and SDMA (Symmetrical Dimethyl Arginine) which are admitted as endothelial dysfunction markers in rat models that are exposed to gamma radiation. Materials and Methods: Twentyfour female Wistar Albino rats were selected for the study. The mean weight of these rats were between 200 and 250 grams. Rats were fed with standard light (12 hours day light /12 hours dark), enough water (ad-libitum) at temperature (25ºC) for a total of 4 weeks. The rats were divided into 4 different groups and each group consisted of 6 rats. controlgroup (group I) did not receive any supplementation and not expose to gamma radiation), Group II was merely exposed to gamma radiation, Group III was exposed to gamma radiation and received vitamin D supplementation, and Group IV merely received vitamin D supplementation. Groups that are given vitamin D supplementation were fed by oral gavage at the same time and every day for one week. Finally, Group II and Group III were exposed to gamma radiation at the 8th day. After the completion of all processes, Vitamin D, ADMA, SDMA and Hcy levels were measured by HPLC (High-performance liquid chromatography) method. Results: When the results of Group II and Group III were compared with each other, we achieved merely statistical significance in vitamin D results (p=0.04) but did not other parameters (p>0.05). Conclusion: We observed that vitamin D supplementation did not any effect on SDMA, ADMA, and Hcy that accompany possible endothelial dysfunction after gamma radiation exposure.